Membrane Transporters as Determinants of the Pharmacology of Platinum Anticancer Drugs - J. Liu, Johnson; Lu, Jun; J. McKeage, Mark (Current Cancer Drug Targets, 2012)
Membrane transporters govern the movement of drugs and their metabolites across biological membranes, thereby determining their pharmacokinetics, efficacy and adverse drug reactions. Platinum-based anticancer drugs are a mainstay of chemotherapy for many human malignancies. However, their clinical utility is limited by tumor resistance and normal tissue toxicities, which are determined at least in part by the level of tissue accumulation of platinum. Recently, several members of the ATP-binding cassette (ABC), solute carrier (SLC) and ATPase membrane protein superfamilies have been found to contribute to the net accumulation of platinum drugs in malignant and normal tissues. Herein, a review has been carried out to critically evaluate current preclinical and clinical evidence implicating membrane transporters as determinants of the pharmacology of cisplatin, oxaliplatin, carboplatin and related investigational compounds. The evidence includes studies of recombinant cell systems with genetically modified expression of individual membrane transporters, platinum-resistant or -sensitive human cancer cells and in vivo xenografted tumors, animal models of platinum-induced nephro-, oto- or neurotoxicity, and clinical studies of associations between the membrane transporter tumor expression and patient outcomes from platinum-based chemotherapy. Understanding the role of membrane transporters as determinants of the pharmacology of platinum drugs will be a basis for targeting these drug transporters in individualized and optimized platinum-based cancer therapy, and new drug development.
Keywords: platinum toxicity